Occupational Safety And Health (Osh) From Islamic Perspective: A Conceptual Study - Ismail, Afifah Binti; Bin Ahmad Razimi, Mohd Shahril (IKONOMIKA, 2018)
ABSTRACTThis paper illustrates occupational safety and health (OSH) based on Islamic perspective in human resource management. This paper has been written based on the following objectives; a)to state the duty of employer to provide safety workplace and to concern on employee health; b)to list out the management system of OSH based on Islamic perspective as preventive measure.A purely qualitative approach of literature review was done and Islamic OSH is derived from Islamic principles which are guide by Al-Quran and sunnah. The responsibility to preserve safety and health of employee does not only relies to the employer solely but involved all workers, the government and the authority bodies as the runner for the Occupational safety and Health Act  OSHA 1994, Islamic order’s and policy to be implemented in the organization. The Occupational Safety and Health Master Plan (OSHMP) 2020 is a tremendous incentive by the Ministry of Human Resource to cope and minimize the number of accident and injuries in Malaysia.  Keywords: Islamic occupational safety and health, employee safety and health, Islamic management system of OSH